The effect of temperature on photosystem II efficiency across plant functional types and climate - P. Neri; L. Gu; Y. Song (Biogeosciences, 2024)
Modeling terrestrial gross primary productivity (GPP) is central to predicting the global carbon cycle. Much interest has been focused on the environmentally induced dynamics of photosystem energy partitioning and how improvements in the description of such dynamics assist the prediction of light reactions of photosynthesis and therefore GPP. The maximum quantum yield of photosystem II (ΦPSIImax) is a key parameter of the light reactions that influence the electron transport rate needed for supporting the biochemical reactions of photosynthesis. ΦPSIImax is generally treated as a constant in biochemical photosynthetic models even though a constant ΦPSIImax is expected only for non-stressed plants. We synthesized reported ΦPSIImax values from pulse-amplitude-modulated fluorometry measurements in response to variable temperatures across the globe. We found that ΦPSIImax is strongly affected by prevailing temperature regimes with declined values in both hot and cold conditions. To understand the spatiotemporal variability in ΦPSIImax, we analyzed the temperature effect on ΦPSIImax across plant functional type (PFT) and habitat climatology. The analysis showed that temperature's impact on ΦPSIImax is shaped more by climate than by PFT for plants with broad latitudinal distributions or in regions with extreme temperature variability. There is a trade-off between the temperature range within which ΦPSIImax remains maximal and the overall rate of decline of ΦPSIImax outside the temperature range such that species cannot be simultaneously tolerant and resilient to extreme temperatures. Our study points to a quantitative approach for improving electron transport and photosynthetic productivity modeling under changing climates at regional and global scales.